Genomic characterisation of the thermoadaptation strategies in the penguin genus Eudyptes - Jackson, Debora (My University, 2022)
Penguins are some of the most well adapted vertebrates with regards to cold. They have managed to achieve this through maintaining thermal balance by reducing the amount of heat lost to the environment and by increasing heat production within the body through the use of various behavioural, physiological and molecular mechanisms. The genus Eudyptes is the most specious group within the family Spheniscidae and these species inhabit a range of different thermal environments ideal for studying the molecular mechanisms that drive coldadaptation. This study aimed to investigate the molecular determinants underlying thermoregulatory adaptation and their evolution among Eudyptes penguin species from different thermal environments. A phylogenetic assessment was undertaken using two approaches. Orthologous and paralogous proteins were identified, annotated and classified to their function and gene ontology using OrthoFinder and EggNOG-mapper. Amino acid analysis and selection analysis were then undertaken on proteins that were found to have a putative role in thermoregulation using BaCoCa and the Selection Server, respectively. The penguins that inhabited sub-Antarctic environments were shown to form a clade in both core genome ML phylogeny and a house-keeping gene ML phylogeny that consisted of the macaroni and royal penguins. A clade was also formed with the penguins that occupy temperate environments i.e. the temperate climate penguin clade, composed of the southern rockhopper, eastern rockhopper, northern rockhopper, Fiordland, snares and erect-crested penguins. This temperate climate clade was further divided into two sub-clades. When the Eudyptes pan-genome was compared with the yellow-eyed penguin (outgroup), 16,511 orthogroups were identified and of these approximately 60% were shared among the nine compared taxa (core proteins). The unique proteins in the cold climate penguin clade only made up 1.28% of the total pan-genome complement compared to the 10.9% that were found in the temperate climate penguin clade. Thirty-five of these unique proteins found in the cold climate Eudyptes penguins play potential roles in various thermoadaptation and thermoregulation strategies. Paralogous proteins were then investigated among the temperate climate and cold climate penguin clades to discover whether they play a potential role in cold-adaptation as gene duplication may serve as a mechanism for tolerating cold stress, especially in penguins. Approximately 19.4% of the total pan-genome protein complement comprised paralogous copies, of which 90 were found to be over-represented in the cold clade penguins by > two-fold relative to the temperate climate penguins. Of these, thirteen were linked to a potential role in thermoregulation with TUBA1C having the most copies present in the macaroni penguin compared to the temperate climate penguins. 90 Single copy orthologous proteins conserved in both cold and temperate clade penguins were subjected to microevolutionary scale analysis at the individual protein and gene level. SCOs contributed nearly 47% of the Eudyptes pan-genome complement. Through amino acid bias analysis, biases in the SCO aligned aa sequence data were identified using various statistical tests (RCFV, chi-square and p-value). Fourteen SCOs met at least one of the statistical cut-off criteria and were found to be linked to thermal regulation. Furthermore, two were discovered to be under overall positive selection (DLL4 and FADS1). Amino acid composition of the fourteen candidate thermoregulation proteins (as is supported in the literature) revealed that cold-adapted proteins prefer conformational flexibility over conformational stability. This is then achieved through an increase in the number of small, neutral amino acids such as serine as well as amino acids that increase the solubility of a protein i.e. aspartic acid. These observed changes are modest but may have a large potential impact on protein function in cold conditions regardless. All these analyses have shown that various molecular mechanisms can be linked to main thermoregulatory mechanisms such as glucose metabolism, lipid metabolism, adipocyte differentiation, vascular development, feather development and skeletal muscle functioning. There are a few limitations to this study. Without looking at other factors such as morphology, integumentary data and behavioural data we cannot definitively say that all eight Eudyptes species are separate species, but our molecular data does suggest this is the most likely case. Another limitation is that many proteins still need to be fully functionally evaluated and annotated and many more proteins may play a role in thermoregulation and thermoadaptation. As a result, they may provide more information on mechanisms that help in cold adaptation. Future studies should incorporate all extant penguin species, especially the species localised in Antarctica i.e. the emperor and king penguins, and by the equator (the Galápagos penguin) to get an even more in-depth account of cold adaptation in penguins. Studies could also look at molecular mechanisms in their temperate counterparts in order to see how climate change may affect the different taxa. In conclusion, this study provides primary information in order to start uncovering the molecular mechanisms that allow penguins to inhabit various environments as well as to uncover the molecular mechanisms that drive cold adaptation in penguins.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Molecular and Cell Biology to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Genomic characterisation; Thermoadaptation strategies; Penguin genus Eudyptes